2020
DOI: 10.35207/later.729713
|View full text |Cite
|
Sign up to set email alerts
|

Yabancı Dil Sınıf Kaygısı Ölçeği’nin Faktör Yapısının İncelenmesi

Abstract: Foreign language anxiety has been the subject of research for many years as one of the individual factors affecting the language learning process. In this study, the factor structure of Foreign Language Anxiety Scale was examined in the context of Turkey. The study group consisted of 166 students studying in the English preparatory department of a university in the Marmara Region during the spring semester of the 2017-2018 academic year. Validity and reliability study consists of language validity, scoring, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The Rasch model is characterized by robustness and objective assessment of latent traits [ 39 ], which is why this model was chosen to analyse the ELAS. The Results of the present study indicate that ELA is a multi-dimensional construct, and recent data support these findings [ 4 , 5 , 44 ]. The main aim of this paper was to examine the psychometric properties of the ELAS using the Rasch rating scale model and then detecting the DIF across sex.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The Rasch model is characterized by robustness and objective assessment of latent traits [ 39 ], which is why this model was chosen to analyse the ELAS. The Results of the present study indicate that ELA is a multi-dimensional construct, and recent data support these findings [ 4 , 5 , 44 ]. The main aim of this paper was to examine the psychometric properties of the ELAS using the Rasch rating scale model and then detecting the DIF across sex.…”
Section: Discussionsupporting
confidence: 87%
“…It is well-documented in the literature that FLA is a multi-dimensional construct [ 2 , 3 , 10 ]. However, other studies have found that FLA may consist of three dimensions: speaking anxiety, failure anxiety and lack of self-confidence [ 44 ]. Lack of self-confidence and fear of making mistakes are possible reasons for speaking anxiety, which tends to appear in shy students who feel uncomfortable because of the communication requirements.…”
Section: Ela In the Egyptian Contextmentioning
confidence: 99%
“…Consequently, researchers have employed different components of anxiety to assess foreign language anxiety. One such study conducted by Oruç and Demirci (2020), who had a similar sample group to ours, identified three components: speech anxiety, failure anxiety, and low self-confidence. Speech anxiety refers to the strain experienced when conversing with others, failure anxiety involves the belief of being unable to complete the language learning process successfully, and low self-confidence reflects a lack of belief in one's language learning abilities.…”
Section: Foreign Language Anxiety and Beliefs Towards Learning A Fore...mentioning
confidence: 64%
“…Communication anxiety relates to difficulties in speaking within a group, test anxiety involves the fear of failure, and negative evaluation anxiety entails the belief that one will be negatively judged by others. However, previous studies on foreign language anxiety have revealed that the components of foreign language anxiety may vary across different cultural contexts (Oruç & Demirci, 2020). Consequently, researchers have employed different components of anxiety to assess foreign language anxiety.…”
Section: Foreign Language Anxiety and Beliefs Towards Learning A Fore...mentioning
confidence: 99%